Population dynamics and the influence of hydrology on nonnative rainbow trout in a perialpine limestone stream - Kurt Pinter; Marlene Kollmann; Erwin Lautsch; Günther Unfer (Global Ecology and Conservation, 2025)
Rainbow trout, originally from Pacific coast catchments (North America), have been distributed extensively on a global scale for consumptive and recreational fishing. Consequently, the species now occurs widely in freshwater ecosystems around the world. The reasons for the success or failure of self-sustaining populations that settle in watersheds outside of their natural range have been the subject of debate for decades. This study investigates the establishment and persistence of a rainbow trout population in a perialpine central European stream. Our analysis combines hydrological data with a 27 year-long time series (1997–2023) of annual data on the abundance of sympatric rainbow trout and brown trout populations. Despite the cessation of fish stocking since 1997, rainbow trout persist as a self-sustaining and robust population. A number of stream characteristics are hypothesized as critical to their persistence in this stream. First, high pre-spawn flows generally lead to enhanced recruitment of rainbow trout. This pattern likely results from the flushing of substrate sediments, thus improving the quality of spawning habitat. Conversely, high discharge during the fry-emergence period negatively impacts juvenile densities. Rainbow trout exhibit higher relative production of juvenile fish compared to native brown trout but experience a sharp decline in densities from young of the year to age 1 + class. This decline can be attributed to either mortality or outmigration of rainbow trout from the stream reach due to the predominance of native brown trout – the numerically dominant species (66 %) in the study area. Although brown trout remain dominant within the study’s stream reach, our study highlights the potential of rainbow trout’s invasiveness demonstrated by a consistently positive population trend and emphasizes the need for increased vigilance towards this species, relative to the native brown trout.